Occurrence of Banana bunchy top virus in banana and plantain (Musa sp.) in Benin - Lokossou, B.; Gnanvossou, D.; Ayodeji, O.; Akplogan, F.; Safiore, A.; Migan, D.; Pefoura, A.; Hanna, R.; Kumar, P. Lava (Wiley, 2012)
In July 2011, banana and plantain that displayed stunting and leaf symptoms typical of banana bunchy top disease were observed to be widespread in Dangbo Commune, Ouémé Department, Benin. To identify the cause of the disease, a roving survey was conducted in December 2011 in nine locations in Avrankou, Dangbo, Akpro-Missérété and Porto-Novo Communes, in Ouémé. In each location, the incidence of symptom-bearing plants was estimated from counts of 15 mats, and samples were collected for Banana bunchy top virus (BBTV) assessment. Approximately 60% of the 94 banana mats assessed had plants exhibiting typical symptoms of BBTV infection - chlorotic leaf margins, dark green streaks on petioles, narrow leaves that bunched at the top, and severe stunting. Total DNA was extracted from 25 leaf samples collected from plants with symptoms; they were then tested for BBTV by polymerase chain reaction. The sequences showed 100% nucleotide sequence identity with a BBTV isolate from Cameroon (FJ580970) and 99-100% identity with several other BBTV isolates from the GenBank database belonging to the South Pacific group, which consisted of BBTV isolates from Africa, Australia, India and South Pacific. This finding confirmed that the virus isolate associated with the diseased plants in Benin was of the BBTV South Pacific type. This is thought to be the first report of BBTV in Benin. The disease is widespread in all the four communes surveyed.